Photosynthesis Productivity Improvement Efficiency and Yield in Salt Soils - Ikramova, M L; Raxmatov, B N; Maxsudov, S I; Yunusov, R; Karimova, M F (Discoveries in Agriculture and Food Sciences, 2024)
The article provides data on how to increase the growth and development of cotton, yield, photosynthesis productivity, restore soil fertility, reduce salinity, pH of the alkaline environment in saline, arid zones of the Bukhara oasis. In the 6th variant, when using “Carbon dioxide forming a utility model” during the plowing period and after 1-2 irrigations in cotton, the exhaust gas introduced under the soil turned out to be the most effective, due to this, the formed carbonic acid normalized the balance of soil microorganisms, reduced salinity by 52.09%, neutralized alkalinity after washing salts from pH=8.1 (in control) to 6-var. pH = 7.5 converted hard-to-reach phosphorus into digestible forms for plants, leaf area increased by 0.6805 m2/ plant, dry weight- 320 g, net photosynthesis productivity- 10.4 g/ m2, additional yield- 15.7q / ha, weight of one bolls- 7.4g, weight 1000pcs. cotton seeds-140g, fiber length-37.5 mm, fiber yield-39%. Profitability- 34-40%.